SLE and Non-Hodgkin’s Lymphoma: A Case Series and Review of the Literature - Prajwal Boddu; Abdul S. Mohammed; Chandrahasa Annem; Winston Sequeira (Case Reports in Rheumatology)
Systemic lupus erythematosus (SLE) is a multisystem autoimmune disorder punctuated by varied multiorgan complications all along the course of its natural history. Lymphoma represents a relatively well-recognized malignant phenomenon associated with lupus. The cause and effect relationships of lymphoma in SLE have been subject to extensive scrutiny with several studies reporting on clinic-pathologic characteristics and risk factors predicting lymphoma development in SLE. However, the pathogenic role of immunosuppressives in SLE-related lymphoma still remains unclear, and indices to help guide diagnosis, prognostication, therapy, and posttreatment monitoring are yet to be established. In this review, we describe 3 SLE patients who developed non-Hodgkin’s lymphoma at different time points of their disease. Through a careful dissection of the aforementioned cases, we intend to apprise readers of the currently available literature surrounding risk factors, management, and prognosis in SLE-related lymphoma. We will also review and discuss the implications of immunosuppressives in SLE-related lymphoma and the role of mycophenolate mofetil in SLE-related primary CNS lymphoma development.